Mechanistic characterization of insecticidal Shiva toxin interactions with Drosophila melanogaster nicotinic acetylcholine receptors - Kyle D. Schneider; Joseph Tourtois; Daniel Bertrand; Kumiko Kambara; Daniel Hulbert; Alexandra Haase; Sophia R. Kanniainen; Brian DeVree; Robert M. Kennedy; Lin Bao (Pesticide Biochemistry and Physiology, 2026)

Antioxidants green tea extract and nordihydroguaiaretic acid confer species and strain-specific lifespan and health effects in Caenorhabditis nematodes - Stephen A. Banse; Christine A. Sedore; Erik Johnson; Anna L. Coleman-Hulbert; Brian Onken; David Hall; E. Grace Jackson; Phu Huynh; Anna C. Foulger; Suzhen Guo; Theo Garrett; Jian Xue; et al. (GeroScience, 2023)
The Caenorhabditis Intervention Testing Program (CITP) is an NIH-funded research consortium of investigators who conduct analyses at three independent sites to identify chemical interventions that reproducibly promote health and lifespan in a robust manner. The founding principle of the CITP is that compounds with positive effects across a genetically diverse panel of Caenorhabditis species and strains are likely engaging conserved biochemical pathways to exert their effects. As such, interventions that are broadly efficacious might be considered prominent compounds for translation for pre-clinical research and human clinical applications. Here, we report results generated using a recently streamlined pipeline approach for the evaluation of the effects of chemical compounds on lifespan and health. We studied five compounds previously shown to extend C. elegans lifespan or thought to promote mammalian health: 17α-estradiol, acarbose, green tea extract, nordihydroguaiaretic acid, and rapamycin. We found that green tea extract and nordihydroguaiaretic acid extend Caenorhabditis lifespan in a species-specific manner. Additionally, these two antioxidants conferred assay-specific effects in some studies—for example, decreasing survival for certain genetic backgrounds in manual survival assays in contrast with extended lifespan as assayed using automated C. elegans Lifespan Machines. We also observed that GTE and NDGA impact on older adult mobility capacity is dependent on genetic background, and that GTE reduces oxidative stress resistance in some Caenorhabditis strains. Overall, our analysis of the five compounds supports the general idea that genetic background and assay type can influence lifespan and health effects of compounds, and underscores that lifespan and health can be uncoupled by chemical interventions.

Dependence on a human structure influences the extinction of a non-native lizard population after a major environmental change - Daniel A. Warner; Joshua M. Hall; Amélie Fargevieille; Austin C. Hulbert; Sarin Tiatragul; Jenna E. Pruett; Timothy S. Mitchell (Biological Invasions, 2021)

Use of human-made structures facilitates persistence of a non-native ectotherm - Austin C. Hulbert; Joshua M. Hall; Timothy S. Mitchell; Daniel A. Warner (Biological Invasions, 2020)

Automated lifespan determination across Caenorhabditis strains and species reveals assay-specific effects of chemical interventions - Stephen A. Banse; Mark Lucanic; Christine A. Sedore; Anna L. Coleman-Hulbert; W. Todd Plummer; Esteban Chen; Jason L. Kish; David Hall; Brian Onken; Michael P. Presley; E. Grace Jones; Benjamin W. Blue; et al. (GeroScience, 2019)
The goal of the Caenorhabditis Intervention Testing Program is to identify robust and reproducible pro-longevity interventions that are efficacious across genetically diverse cohorts in the Caenorhabditis genus. The project design features multiple experimental replicates collected by three different laboratories. Our initial effort employed fully manual survival assays. With an interest in increasing throughput, we explored automation with flatbed scanner-based Automated Lifespan Machines (ALMs). We used ALMs to measure survivorship of 22 Caenorhabditis strains spanning three species. Additionally, we tested five chemicals that we previously found extended lifespan in manual assays. Overall, we found similar sources of variation among trials for the ALM and our previous manual assays, verifying reproducibility of outcome. Survival assessment was generally consistent between the manual and the ALM assays, although we did observe radically contrasting results for certain compound interventions. We found that particular lifespan outcome differences could be attributed to protocol elements such as enhanced light exposure of specific compounds in the ALM, underscoring that differences in technical details can influence outcomes and therefore interpretation. Overall, we demonstrate that the ALMs effectively reproduce a large, conventionally scored dataset from a diverse test set, independently validating ALMs as a robust and reproducible approach toward aging-intervention screening.